2005
DOI: 10.1677/jme.1.01702
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of sex steroid hormones on the expression of multiple first exons including a novel first exon of prolactin receptor gene in the rat liver

Abstract: In addition to the known four alternative first exons E1 1 , E1 2 , E1 3 and E1 4 of the rat prolactin receptor (PRL-R) gene, a novel first exon, E1 5 , was identified by cDNA cloning of the 58-end region of PRL-R mRNA in the rat liver. Genomic fragments containing E1 5 and its 58-or 38-flanking regions were also cloned from rat kidney genomic DNA. A sequence search for E1 5 revealed that E1 5 is located 49 kb upstream of exon 2 of the PRL-R gene in rat chromosome 2q16. RT-PCR analysis revealed that E1 5 was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 27 publications
1
20
0
Order By: Relevance
“…the E1 3 variant is expressed generically in a wide range of tissues [18], whereas the E1 4 variant is expressed preferentially in the cerebrum, including the choroid plexus [27,34]. the E1 5 variant is transcribed in the brain, liver, and kidney [35]. Previously, we showed that PrLr gene expression in the rat cerebrum increased during lactation in female rats while the postnatal development of male and female rats depended on the transcriptional activation of E1 4 [20,34].…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…the E1 3 variant is expressed generically in a wide range of tissues [18], whereas the E1 4 variant is expressed preferentially in the cerebrum, including the choroid plexus [27,34]. the E1 5 variant is transcribed in the brain, liver, and kidney [35]. Previously, we showed that PrLr gene expression in the rat cerebrum increased during lactation in female rats while the postnatal development of male and female rats depended on the transcriptional activation of E1 4 [20,34].…”
Section: Introductionmentioning
confidence: 94%
“…in mammals, PRLR gene expression is regulated via the transcriptional activation of multiple alternative first exons that encode 5'-untranslated regions. Five first exons have been identified in the rat PRLR gene, i.e., E1 1 , E1 2 , E1 3 , E1 4 , and E1 5 [16,22,34,35]. the E1 1 variant of PRLR mRNA is expressed specifically in gonadal tissues [17], whereas the E1 2 variant is transcribed in the liver and kidney [22,35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In rat Prlr gene, five alternative first exons, E1 1 , E1 2 , E1 3 , E1 4 , and E1 5 , have been identified previously (Hu et al 1996, Moldrup et al 1996, Tanaka et al 2002. In rats, the E1 1 variant of Prlr mRNA is specifically expressed in the gonadal tissues (Hu et al 1997) and the E1 2 variant is transcribed in the liver and kidney (Moldrup et al 1996, Tanaka et al 2005. In addition, the E1 3 variant is expressed in a wide range of tissues (Hu et al 1998), whereas the E1 4 variant is preferentially expressed in the brain (Tanaka et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the E1 3 variant is expressed in a wide range of tissues (Hu et al 1998), whereas the E1 4 variant is preferentially expressed in the brain (Tanaka et al 2002). Finally, the E1 5 variant is used in the brain, liver, and kidney (Tanaka et al 2005). In murine Prlr gene, three first exons homologous to rat E1 1 , E1 2 , and E1 3 (referred to as mE1 1 , mE1 2 , and mE1 3 respectively) have been detected to date (Davis & Linzer 1989, Hu et al 1997.…”
Section: Introductionmentioning
confidence: 99%